How does happiness affects women entrepreneurs’ success? - Dwi Prasetyani; Amelia Choya Tia Rosalia; Ellytahatin Indah (Sebelas Maret Business Review, 2020)
This study intends to see the meaning of happiness of women entrepreneurs in the business. This research was conducted in the city of Surakarta using qualitative methods with a phenomenological approach and social constructivist perspective. The results showed that happiness that is in line with a successful business is accompanied by a calm heart and mental condition and away from worry and sadness. In achieving happiness, there are supports influenced by both material and non-material aspects. Women entrepreneurs in Surakarta interpret success not only from the material side but also from the peace of mind, such as the absence of worry and fear, which shows that happiness goes in the same direction with success.